New record of bilateral hyperdontia in Carollia brevicauda (Chiroptera: Phyllostomidae) - Esquivel-Melo, Diego; Camelo-Pinzon, Diana; Rodriguez-Bolaños, Abelardo (THERYA, 2017)
Systematics and taxonomy of bats is based in part on the morphological characteristics of the teeth and dental formulas. However, sometimes dental abnormalities appear that involve changes in the shape and number of teeth which can lead to erroneous taxonomic identifications. Numerous cases of dental anomalies have been reported for all groups of mammals, especially bats, the group with the most dental anomalies reported. This note presents a rare case of bilateral hyperdontia in Carollia brevicauda, for which only cases of oligodontia had previously been registered. The dental anomaly was found in a male specimen of silky short-tailed bat from the middle basin Rio Guayuriba, Acacias, Meta, Colombia. The unusual individual shows an additional incisor annexed to each normal external incisor in the maxilla, with separate alveoli, for a total of 6 upper incisors, two more than normal. The extra teeth have a morphology similar to the external incisors characteristic of the species, short and rounded, and are located between the canine and the second (external) upper incisor on each side of the head. No other specimen among 66 individuals of the same species showed a dental anomaly. This is the first record of bilateral hyperdontia for C. brevicauda. This dental anomaly may be due to an isolated mutation in this individual, because no other specimens with this type of anomaly were found in the study area.